The Effect of Green Investment on Firm Value - Debbianita, Debbianita; Prayogo, Enny; Hoetama, Marcella (Jurnal Ekonomi Akuntansi dan Manajemen, 2024)
Indonesia was one of over 40 countries that signed the Global Coal to Clean Power Transition declaration at the 26th Climate Change Summit (COP26) and positioned Indonesia as a key green investment destination. Green Investment is an investment activity that focuses on companies or investment prospects that have a commitment to the conservation of natural resources, the production and discovery of alternative sources of new and renewable energy (EBT), the implementation of clean water and air projects, and investment activities that are friendly to the surrounding environment. Green investment as a company's effort to manage environmental problems by reducing the negative impact of business activities on the environment therefore green investment can increase competitive advantage, reputation, and company value. The implementation of green investment is one of the company's strategies in increasing profits without damaging the environment. This study will use the SRIKEHATI index, measurement of Green investment using PROPER ratings There are 5 levels in the PROPER rating, namely the first rank is given a gold color, the second rank is given a green color, the third rank is given a blue color, the fourth rank is given a red color, and the last rank is given a black color, and the company value can be calculated using Tobins Q calculation. Keywords: Green Investment, Company Value